Polysulfones with Phenylalanine Derivatives as Chiral Selectors – Membranes for Chiral Separation - Isezaki, Jun; Yoshikawa, Masakazu; Li, Nanwen; Robertson, Gilles P.; Guiver, Michael D. (Journal of Membrane and Separation Technology, 2012)
Polysulfone with a derivative of phenylalanyl residue as a chiral selector (PSf-Ac-D-Phe or PSf-Ac-L-Phe) were prepared by polymer reaction of benzylamine-modified polysulfones with N-a-acetyl-D-phenylalanine or N-a-acetyl-L-phenylalanine. Both polysulfones having a chiral selector gave durable self-standing membranes. The specific rotations of those polymers revealed that the chiral selectors were successfully introduced into the polysulfone. PSf-Ac-D-Phe membrane incorporated L-Glu in preference to D-Glu and vice versa. The chiral separation ability was studied by applying a concentration gradient as a driving force for membrane transport. Permselectivities for those two types of membrane reflected their adsorption selectivities. PSf-Ac-D-Phe membrane selectively transported L-Glu and vice versa. Predicted permselectivities by adopting membrane resistance coincided with the observed ones.